Feeling of freedom: singularities of a cooperative experience that seeks to tear down prison walls - Barrera, Yael Yanina (2022)
Introduction The penitentiary emergency, declared in Argentina in 2019 as a corollary of the increase in the incarcerated population, shows the prevalence of the deployment of punitive mechanisms over those who seek the socio-labor inclusion of people who go through and went through confinement contexts. Objective Faced with this complex plot and as an alternative path to prison confinement, we studied a work cooperative that brings together both detained and released people as well as family members and other close ties. Method The base material for the analysis arises in the framework of an investigation that is still ongoing. In this article we work from a qualitative methodological perspective, conducting semi-structured interviews and a case study for which we take the experience of this work cooperative. Following Yacuzzi, "cases are particularly valid when 'how' or 'why' questions arise, when the researcher has little control over events, and when the topic is contemporary" (2005, 4). Results From the analysis it appears that this work cooperative for people who went through confinement contexts, is active in the accompaniment of intra-extra prison walls, pre and post confinement and in multiple areas that this particular population must face. Our intention is to analyze to what extent the cooperative is constituted as an alternative to prison confinement and what are the complex contours that configure these experiences.   [Continue reading in the article]